Ultrasound-Guided Peripheral Venous Access: A Meta-Analysis and Systematic Review. Issue 4 (July 2015) - Stolz, Lori A; Stolz, Uwe; Howe, Carol; Farrell, Isaac J; Adhikari, Srikar
Objectives: The objective of this study was to determine through a systematic review of the literature and meta-analysis whether success rates, time to cannulation, and number of punctures required for peripheral venous access are improved with ultrasound guidance compared with traditional techniques in patients with difficult peripheral venous access. Methods: We conducted a systematic search of MEDLINE, Web of Science, The Cochrane Library, ClinicalTrials.gov, Cumulative Index to Nursing, and Allied Health Literature. Studies were included if they met the following criteria: patients of any age identified as having difficult peripheral venous access; real-time ultrasound guidance was used for peripheral venous cannulation; and inclusion of at least one of these outcomes (success rates, time to successful cannulation and number of punctures required). Results: Seven studies were selected for final analysis. Ultrasound guidance improved success rates when compared with traditional techniques [pooled odds ratio (OR) 3.96; 95% confidence interval (95% CI) 1.75-8.94]. No significant difference between ultrasound-guided techniques and traditional techniques was detected for time to cannulation or number of punctures required. Conclusions: In patients with difficult peripheral venous access, ultrasound guidance increased success rates of peripheral venous placement when compared with traditional techniques. However, ultrasound guidance had no effect on time to successful cannulation or number of punctures required for successful cannulation.